Profile of patients in palliative care treated by physiotherapy in home care at an oncology hospital - Susana Moura Pinheiro; Ernani Costa Mendes (O Mundo da Saúde, 2024)
Population aging and the increase in chronic non-communicable diseases, including cancer, have required the incorporation of Palliative Care (PC) into health care networks. Thus, the objective of this study was to describe the profile of patients in palliative care treated by physiotherapy in home care at an oncology reference hospital. This is a cross-sectional, quantitative, retrospective and descriptive study, analyzing 76 medical records of patients assisted by physiotherapy in the hospital's home care between August 2018 and August 2019. The majority of patients were female (n=51, 67.11%), of black race/color (n=46, 60.52%), aged between 60 and 80 years (n=36, 47, 37%). Breast (n=22, 28.95%), lung (n=11, 14.47%) and prostate (n=8, 10.53%) cancers were the most common and the majority showed disease progression. Finally, the main reason for physiotherapy monitoring was related to functionality and mobility. The characterization of patients who require physiotherapeutic care in home care at an oncology reference hospital is necessary for better care planning as such information can direct therapeutic possibilities, allowing greater effectiveness in treatment.